First report of Zethus schadei (Hymenoptera: Vespidae) as natural enemy of Hypsipyla grandella Zeller (Lepidoptera: Pyralidae) from Colombia - Pulgarín Díaz, John Alexander; Cano Gallego, Lucas Esteban; Herrera-Florez, Andres Fabián; Quiroz Gamboa, Jhon Alveiro (Instituto de Ecología, A.C., 2018)
Zethus schadei Bohart & Stange is reported for the first time for Colombia and as a natural enemy of Hypsipyla grandella. The specimens were obtained from terminal shoots of Cedrela odorata L. (Meliaceae) in a plantation in the municipality of San Roque, Antioquia, Colombia.